The influence of leadership style and job satisfaction on the work discipline of elementary school teachers in gunung batu - Sumiati Sumiati; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
Based on the background, the researcher can identify the problems in Elementary School of Gunung Batu. There are some problem that researcher find. Such as, 1) teacher discipline in teaching is still lacking, 2) headmaster is less concerned with the needs of teachers at work, 3) lack of learning facilities including teacher handbooks,4) teachers take care of proposals for ranks themselves, not coordinated by the school, and 5) there is no reward for teachers whose subjects excel. The hypothesis in this study is that there is an influence of leadership style on the work discipline of Gunung Batu Elementary School teachers. There is an effect of job satisfaction on the work discipline of Gunung Batu Elementary School teachers. There is an influence of leadership style and job satisfaction together on the work discipline of Gunung Batu Elementary School teachers. The data collection is done by observation, interviews and questionnaires. Analysis is conducted correlation analysis t test and F test results of the questionnaire and the data analysis showed that there is leadership style influence on teachers' work Discipline Elementary School 2 Rock amounted to 84.5% with a value of t = 17 489. with sig 0.000. There is an effect of Job Satisfaction on the work discipline of teachers at Gunung Batu 2 Elementary School at 79.7% with a value of t = 14,818. with sig 0.000. There is an effect of Leadership Style and Job Satisfaction together on the work discipline of teachers of SD Negeri 2 Gunung Batu by 86.3% with a value of F = 173,909. with sig 0.000. From a joint comparison, the influence of the leadership style variable is more dominant than job satisfaction, namely 5.183 versus 2.709, so the leadership style variable has a smaller significance, namely 0.000.